Improving Conceptual Knowledge and Soft Skills among Vocational Students through Inquiry-Based Learning in a Flipped Classroom - Haji Hamdan, Muhammad Khairul Kamilin; Salleh, Sallimah M.; Shahrill, Masitah; Asamoah, Daniel (International Journal of Social Learning (IJSL), 2022)
This study investigated the efficacy of inquiry-based learning (IBL) in a flipped classroom in enhancing vocational students’ conceptual knowledge and inquiry skills of vocational students. We conducted IBL interventions in a flipped classroom through a pre-experimental design (i.e., one-group pretest-posttest approach). A total of 14 second-year students of the HNTec in Agro-technology programme in one of the vocational schools in Brunei Darussalam were conveniently sampled. Data were collected through achievement tests and online interviews, and analysed using the paired sample t-test, the Wilcoxon-signed rank test, and thematic analysis. The findings showed that the IBL intervention in a flipped classroom improved the conceptual knowledge and inquiry skills of vocational students. There were significant differences (p=0.001<0.05) between the pretest and posttest scores of students’ conceptual knowledge: declarative, procedural, and semantic, and the dimensions of inquiry skills: observation, questioning, hypothesising, investigation and interpretation. Students reported positive perceptions toward IBL in a flipped classroom although they faced accessibility and adaptability challenges. This study concluded that IBL in a flipped lesson environment enhances the conceptual knowledge and inquiry skills that are fundamental in developing soft skills among vocational students. Recommendations were made based on the need to ensure a simultaneous use of IBL and flipped pedagogical approaches in vocational education.